2015
DOI: 10.1515/eces-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements in Mediterranean Mussels Mytilus galloprovincialis from the South African West Coast

Abstract: TRACE ELEMENTS IN MEDITERRANEAN MUSSELS Mytilus galloprovincialis FROM THE SOUTH AFRICAN WEST COASTPIERWIASTKI ŚLADOWE W ŚRÓDZIEMNOMORSKICH MAŁŻACH Mytilus galloprovincialis Z POŁUDNIOWEGO WYBRZEŻA AFRYKI ZACHODNIEJ Abstract: Invasive bivalve molluscs, Mediterranean mussels (Mytilus galloprovincialis) were used as sentinel biomonitors of pollution by inorganic contaminants in Saldanha Bay and the Langebaan Lagoon area of South Africa. Two complementary analytical techniques, ICP-MS and NAA, allowed for determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
2
9
0
3
Order By: Relevance
“…The authors of the rebuttal demanded that our study should extend to a much wider geographical area. Such studies are available for metal contaminants in mussels in Saldanha Bay versus Danger Bay, which was chosen as a remote control site (Bezuidenhout et al, 2015). Yet their studies showed that metal concentrations were higher at the control site than at the sampling sites Hence control sites in remote locations can also bring surprises.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the rebuttal demanded that our study should extend to a much wider geographical area. Such studies are available for metal contaminants in mussels in Saldanha Bay versus Danger Bay, which was chosen as a remote control site (Bezuidenhout et al, 2015). Yet their studies showed that metal concentrations were higher at the control site than at the sampling sites Hence control sites in remote locations can also bring surprises.…”
Section: Discussionmentioning
confidence: 99%
“…Выбор определяемых элементов был сделан с учетом анализа литературных данных и проведенных нами экспериментальных исследований [4,35]. В иссле-дуемых пробах моллюсков определяли 14 элемен-тов (As, Ba, Cd, Co, Cr, Cu, Fe, Hg, Ni, Pb, V, Sr, Zn, Mn) методом атомно-эмиссионной спектрометрии с индуктивно-связанной плазмой с использованием спектрометра iCAP-6500 (Thermo Scientific, США).…”
Section: таблицаunclassified
“…Располагая данными о накопле-нии тяжелых металлов в теле моллюсков, особенно в створках, можно судить о качестве среды в водо-еме [2][3][4][5][6][7] не только в период съемки, но и за период жизни моллюска. Моллюски рода Mytilus -мидии -широко распространены в Мировом океане [7][8][9][10]; в Черноморско-Азовском бассейне обитает черномор-ская мидия Mytilus galloprovincialis Lamarck, они явля-ются признанными индикаторами антропогенного за-грязнения прибрежных вод Мирового океана, а также применяются в системе биологического контроля ка-чества среды [11].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Our previous studies determined the ranges of elemental concentrations in Mediterranean mussels at different sites in and around Saldanha Bay [13,14]. In the current work, samples of indigenous mussels (CM), alien mussels (MG) and alien oysters (CG) at three key sites in the Saldanha Bay were chosen to be sampled in order to demonstrate the interspecies differences between them and their ability to be used as biomonitors of macro and microelements in the coastal zones.…”
Section: Introductionmentioning
confidence: 99%